211 Non-Canonical NF-Îšb Signalling Promotes Endothelial Proliferation in Response to Low Wall Shear Stress. (3rd June 2016) - Bowden, Neil; Feng, Shuang; Francis, Sheila; Evans, Paul
Abstract : Introduction: Atherosclerotic plaques are predominantly localised to bends and branches of arteries. In contrast to straight regions where the blood exerts unidirectional high frictional drag, known as wall shear stress (WSS) on endothelial cells (ECs), at atheroprone sites ECs are exposed to complex multidirectional low WSS. These forces cause altered gene expression in ECs, leading to enhanced proliferation, apoptosis, inflammation and lesion development. While the canonical NF-ÎºB pathway has been well studied in early atherogenesis, the non-canonical NF-ÎºB pathwayâ€" regulated by proteasomal processing of the precursor p100 to active p52â€"has not been examined directly in this context. Methods and results: To determine the effect of WSS on non-canonical NF-ÎºB activity, human umbilical vein ECs (HUVECs) were exposed to 72 h of low or high WSS and non-canonical NF-ÎºB expression was analysed by Western blotting. Levels of p100, p52, RelB and IKKÎ ± were elevated under low WSS in comparison to high WSS. In addition, exposure to a known non-canonical NF-ÎºB stimulus CD40L revealed exaggerated pathway activity under low WSS. Depletion of p100 by siRNA resulted in a decrease in proliferation in response to low WSS, measured by Western blotting for Ki67 and staining for PCNA. Conclusions: The non-canonical NF-ÎºB pathway is primed by low WSS for enhanced activation in response to physiological stimuli. p100/p52 promoted EC proliferation under low WSS conditions, indicating that this pathway could be targeted in the prevention or treatment of atherosclerosis.